Emotional intelligence and job satisfaction: Mediating role of promotion and moderating effects of turnover intention among employees - Nguyen, Phuoc-Thien; To, Hoai-Thang; Nguyen, Van Thi Le; Tran-Chi, Phuc-Long; Nguyen-Thi, Ngoc-Han (International Journal of Innovative Research and Scientific Studies, 2025)
Emotional intelligence (EI) has been recognized as a critical factor in enhancing job satisfaction and mitigating turnover intention in organizational contexts. This study investigated the influence of EI on multiple facets of job satisfaction, including contingent rewards, coworker relationships, the nature of work, pay, promotion, supervision, and operating conditions. Additionally, the study examined the mediating role of promotion and the moderating role of turnover intention within these relationships. A cross-sectional survey was conducted among 89 employees in Vietnam using random sampling techniques. Data were collected through validated measures and analyzed using partial least squares structural equation modeling (PLS-SEM). The findings indicated that EI significantly and positively influenced various aspects of job satisfaction. Promotion was found to mediate the relationship between EI and job satisfaction, while turnover intention moderated the relationship between EI and coworker support as well as perceptions of the nature of work. These results underscore the importance of emotional competencies in promoting positive work attitudes and reducing employee turnover intentions, particularly within small and medium-sized enterprises.